Seismic response comparison of an existing hospital structure rehabilitated with BRBs or conventional braces. (15th September 2021) - Ballinas, Eriberto; Guerrero, Hector; Terán-Gilmore, Amador; Alberto Escobar, J.
Highlights: Seismic response of an existing structure rehabilitated with BRBs or conventional braces is compared. Four cases were studied: 0) original structure, 1 and 2) structure with BRBs, and 3) with conventional braces. Cases 1 and 2 outperformed Case 3, with Case 2 being superior to the others. It was seen that the configuration of BRBs plays a significant role. On the other hand, the use of conventional braces led to a surprisingly poor performance. Abstract: Conventional braces (CBs) are commonly used for seismic rehabilitation of structures. However, even when these are designed to comply code standards, they can exhibit an unexpectedly poor structural performance during an earthquake event. In this paper, one of these cases is presented and the possible consequences are discussed. A case study hospital is analyzed. It is an actual reinforced concrete structure located in the city of Puebla, Mexico; near the epicenter of the September 19, 2017 earthquake. The structure is a traditional moment-resistant frame building with reduced lateral stiffness and soft storey problems. Three rehabilitation proposals are analyzed and discussed. For Cases 1 and 2, the building was equipped with buckling-restrained braces (BRBs) using different configurations. For Case 3, a conventional bracing system was considered. The seismic response of the existing building before rehabilitation was also studied as a benchmark (Case 0). Results showed that Cases 1 and 2 outperformed Case 3, with Case 2 being superior to the others. On one hand, it was observed that the configuration of BRBs plays a significant role in the structure's energy dissipating capacity. On the other hand, the use of conventional braces led to a surprisingly poor performance during the earthquake simulations, generating soft storey problems due to premature buckling of the braces.